The problem of ritual efficacy - Sax, William Sturman; Quack, Johannes; Weinhold, Jan (Oxford ritual studies, 2011)
How do rituals work? Although this is one of the first questions that people everywhere ask about rituals, little has been written explicitly on the topic. In The Problem of Ritual Efficacy, nine scholars address this issue, ranging across the fields of history, anthropology, medicine, and biblical studies. For "modern" people, the very notion of ritual efficacy is suspicious because rituals are widely thought of as merely symbolic or expressive, so that - by definition - they cannot be efficacious. Nevertheless people in many cultures assume that rituals do indeed "work